THE EFFECT OF SOCIAL CAPITAL ON THE FOOD SECURITY OF MEMBERS OF THE “MELATI PUTIH” SUSTAINABLE FOOD HOUSE (KRPL) AREA IN BANDUNGREJOSARI, SUKUN DISTRICT, MALANG CITY - Silfi Novita Sari; Sugeng Riyanto; Bayu Adi Kusuma (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Social capital can affect realizing food security, especially if the household joins an organization or group. One example is KRPL